Evaluation of Physical and Chemical Properties of Pomelo (Citrus grandis L.) Essential Oil using Steam Distillation Process - Kim Ngan, Tran Thi; Muoi, Nguyen Van; Quan, Pham Minh; Cang, Mai Huynh (Asian Journal of Chemistry, 2020)
This study attempted the extraction of essential oils from the peels of pomelo (Citrus grandis L.) grown in Ben Tre province, Vietnam through hydrodistillation method. In addition, the chemical composition and physio-chemical properties of the essential oils were reported. The results showed that the extraction yield of the extraction process achieved about 1.67%. The physico-chemical index of essential oils is determined by specific gravity (0.8572 g/cm3), acid index (0.3556 mg KOH/g), ester index (2.4216 mg KOH/g), and refractive index (1.476). The GC-MS analyses of the oil indicated the component with highest content in the oil was α-limonene (96.491%), followed by α-pinene (0.686%), b-pinene (0.248%), b-myrcene (1.644%), α-phellandrene (0.793%) and b-cis-ocimene (0.138%). These results suggested that wastes from fruit peeling process can be converted into a new material source with great potential for industrial use.